Synthesis of Polyaniline/Graphene Oxide/Azobenzene Composite and Its Adjustable Photoelectric Properties - Yanhua Teng; Shiqin Li; Changguo Xue; Hongyan Zhang; Lingkai Zhu; Yu Tang (Advances in Polymer Technology)
Azobenzene derivatives have fast light response characteristics; in this paper, a new azobenzene derivative (Azo) was synthesized and to be made a composite (PANI/GO/Azo) with polyaniline/graphene oxide (PANI/GO). Both composites were carefully investigated by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and thermogravimetric analysis (TGA). Moreover, their electrochemical properties were characterized by the electrochemical workstation, including cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), cycling stability, and electrochemical impedance spectroscopy (EIS). The results demonstrated that the PANI/GO/Azo composite has a higher capacitance of 478.3 F g−1 than that of PANI/GO (359.9 F g−1) at a current density of 1 A g−1. PANI/GO/Azo composite showed excellent photosensitive electrochemical properties under UV irradiation, and its rate of capacitance change achieved about 52.57%. Additionally, the PANI/GO/Azo composite also displayed high reversibility, with specific capacitance retention of 92% after 500 cycles. Therefore, the PANI/GO/Azo electrode with a controllable electrochemical performance by UV irradiation had a great potential in the photoresponsive supercapacitor.